A methodological approach for dynamic modelling of membrane integrated biosorption: a case study on Sphaerotilus natans as biosorbent. (17th October 2008) - Beolchini, F.; Pagnanelli, F.; Toro, L.; Veglio, F.
This work is a review of the study performed on heavy metals biosorption by Sphaerotilus natans confined in an ultrafiltration membrane module. A methodological approach has been applied aiming at the dynamic modelling of the process: i) firstly, biosorbent was characterised according to acid-base properties of binding sites; ii) then, equilibrium studies were performed both in single metal and multimetal systems in order to evidence any competition for binding sites and to find mechanicistic models that are able to describe biosorption equilibrium; iii) finally, biosorption in membrane processes was investigated in laboratory scale, in the case of both single-metal and two-metal systems, and a dynamic model was developed accounting for binding site competition and for binding ability of cell's fragments generated by tangential flow shear stress.